Colonial/Postcolonial Chronotopes in Pramoedya Ananta Toer's The Girl from the Coast. Issue 1 (2nd January 2017) - Niekerk, Carl
ABSTRACT: This essay uses Mikhail Bakhtin's notion of the "chronotope" to analyze the little-known novel The Girl from the Coast (written 1962; first published 1987) by the Indonesian author Pramoedya Ananta Toer (1925–2006). It identifies three specific chronotopes—the house in the city, the village, and the road—which structure the narrative. Each of these chronotopes represents a stage in the development of the novel's anonymous female protagonist, who has grown up in a small village on Java's coast and at the age of 14 is handed over by her parents to a nobleman in the city to become his "practice wife." By breaking out of her spatial marginalization, the protagonist simultaneously also develops a more complex sense of time, not only through an awareness of her country's troubled past, but also of its future potential. The novel can be read as a critique of power structures not only in place during colonial times, but also in Indonesia after its declaration of independence.